PENDAMPINGAN UMKM LONTONG TUYUHAN DENGAN INOVASI PHOTO BOOTH DI DESA TUYUHAN KECAMATAN PANCUR KABUPATEN REMBANG - Rikah Rikah; Ahmad Jumali; Eva Setyaningrum (Buletin Abdi Masyarakat, 2023)
Tuyuhan Village has a lot of tourism diversity in the culinary, religious or educational fields. According to the 2020 Integrated Social Welfare Data from the Rembang District Social Service Office PPKB, Tuyuhan Village is a poor or red village group in Rembang Regency. Mentoring is an activity in community empowerment by placing assistants who act as facilitators, communicators, and dynamicators. In this case, the business group that is used as the object of assistance for Community Service activities through entrepreneurship is the Lontong Tuyuhan Association in Tuyuhan Village, Pancur District, Rembang Regency. The problems faced by the Lontong Tuyuhan Association include a lack of knowledge about making photo booths, the absence of a trademark, the absence of a business management Google account and social media accounts. Based on these problems, the Community Service Team planned a training program for making photo booths, assisting in trademark submissions, creating gmail accounts, creating Instagram social media accounts. The results of the implementation of the program by the Community Service Team together with the Lontong Tuyuhan Association, namely training in making a photo booth so that they can practice the process of making a photo booth, submitting a trademark, creating a special gmail account to manage a business, creating an Instagram social media account.Keywords: Mentoring, Lontong Tuyuhan, Inovation.